An Existentialism Analysis of Chekhovâ€™s Main Characters Smirnov in â€œThe Bearâ€, Lomov in â€œThe Proposalâ€ and Ivan in â€œA Tragedian In Spite Of Himselfâ€ - Aminatuzzuhriyyah -; Wijayadi -; Pramudana Ihsan (Tell : Teaching of English Language and Literature Journal, 2016)
This study is attempted to analyze an existentialism of Chekhovâ€™s main characters Smirnov in â€œThe Bearâ€, Lomov in â€œThe Proposalâ€ and Ivan in â€œA Tragedian in Spite of Himselfâ€. The data are taken from the dialogues selected in the plays mentioned. There are two objectives of the study that are: to find how the main characters show their existence; and to reveal why the main characters doing so in the plays. Descriptive qualitative is applied as research method, while existentialism as the main theory and positivism and rationalism as the supporting theory. This Study found out how the main characters oppose positivism and rationalism by being subjective. Each character has their own way in showing their existence. As the result, every character has their own purposes to be existence. The purposes of the main characters are their own eternal happiness. In â€œThe Bearâ€ Smirnov is being stubborn because he wants to show his power as a landowner, in â€œThe Proposalâ€Â  Lomov is flaunting his wealth in order to propose Natalya, and Ivan is nagging to get sympathy from his friend.